Teori Konsumsi Islam : Refleksi Pemikiran Imam Al-Ghazali Dan Relevansinya Dengan Perilaku Konsumsi Kontemporer - Salimudin, Mumud; Janwari, Yadi; Heryana, Rudy (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze Imam al-Ghazali's economic thoughts on maslaha and its relation to Islamic consumption ethics and its relevance to the consumption behavior of contemporary society. The research methodology used is a qualitative method with a comprehensive type of literature review. The results showed that when it comes to consumer behavior, top priority should be given to primary needs (ḍharuriyyah), followed by secondary needs (hajjiyat) and tertiary needs (taḥsiniyyah) according to the principles of al-maqaṣid al-shari'ah. According to the Islamic perspective, consumption behavior should be to use wealth according to needs and refrain from the nature of israf and tabżir. In every act of consumption, Muslims are obliged to uphold the principles of halal and ṭhayyib. The purpose of consumption behavior in Islamic economics is to satisfy material and spiritual aspects, namely the achievement of goodness both in the world's life and the hereafter called Falah. Both aspects will be achieved by maximizing the benefits of each item consumed